Nutritional evaluation of non-conventional feed resources from wasteland and its effect on yield, chemical composition and inter-relationship between constituents of goat milk - KOUSHKI, M R; GUPTA, M P; OGRA, J L (The Indian Journal of Animal Sciences, 2013)
All non-conventional forages evaluated in the present study were palatable to goats. The control feed had higher crude protein, energy, ether extract and calcium while the non-convenuonal forages contained a higher per cent of crude fibre, nitrogen-free extract and ash. The digestibility of nutrients except that ofother extract was higher on non-conventional forage feeding than on control. Leucaena leucocephala possessed highest nutritive value among non-convcntional forages, and its nutritive value was about similar to that of control feed. Under various feeding regimens, milk yield was significantly (p